Enrichment of CCR6+CD8+ T cells and CCL20 in the lungs of mechanically ventilated patients with COVID‐19. Issue 6 (11th May 2021) - Saris, Anno; Reijnders, Tom D.Y.; Reijm, Martine; Hollander, Jolien C.; de Buck, Kim; Schuurman, Alex R.; Duitman, JanWillem; Heunks, Leo; Aman, Jurjan; Bogaard, Harm Jan; Nossent, Esther J.; van der Poll, Tom; et al.
Abstract : Despite high levels of CXCR3 ligands in mechanically ventilated COVID‐19 patients, BALF CD8 T cells were not enriched in CXCR3 + cells but rather CCR6 +, likely due to high CCL20 levels in BALF, and had very high PD‐1 expression. In mechanically ventilated, but not ward, patients Th‐1 immunity is impaired. ​